Screening of rosmarinic acid from Salvia miltiorrhizae acting on the novel target TRPC1 based on the 'homology modelling–virtual screening–molecular docking–affinity assay–activity evaluation' method. (31st December 2023) - Quan, Wei; Wang, Yuan; Chen, Yu-han; Shao, Qing; Gong, Yang-ze; Hu, Jie-wen; Liu, Wei-hai; Wu, Zi-jun; Wang, Jie; Ma, Shan-bo; Li, Xiao-qiang
Abstract: Context: Salvia miltiorrhizae Bunge (Lamiaceae) is a traditional Chinese medicine (TCM) for the treatment of 'thoracic obstruction'. Transient receptor potential canonical channel 1 (TRPC1) is a important target for myocardial injury treatment. Objective: This work screens the active component acting on TRPC1 from Salvia miltiorrhizae . Materials and methods: TCM Systems Pharmacology Database and Analysis Platform (TCMSP) was used to retrieve Salvia miltiorrhiza compounds for preliminary screening by referring to Lipinski's rule of five. Then, the compound group was comprehensively scored by AutoDock Vina based on TRPC1 protein. Surface plasmon resonance (SPR) was used to determine the affinity of the optimal compound to TRPC1 protein. Western blot assay was carried out to observe the effect of the optimal compound on TRPC1 protein expression in HL-1 cells, and Fura-2/AM detection was carried out to observe the effect of the optimal compound on calcium influx in HEK293 cells. Results: Twenty compounds with relatively good characteristic parameters were determined from 202 compounds of Salvia miltiorrhiza . Rosmarinic acid (RosA) was obtained based on the molecular docking scoring function. RosA had a high binding affinity to TRPC1 protein (KD value = 1.27 µM). RosA (50 μM) could reduce the protein levels (417.1%) of TRPC1 after oxygen-glucose deprivation/reperfusion (OGD/R) in HL-1 cells and it could inhibit TRPC1-mediated Ca 2+ influx injury (0.07 ΔRatio340/380) in HEK293 cells. Discussion and conclusions: We obtained the potential active component RosA acting on TRPC1 from Salvia miltiorrhizae, and we speculate that RosA may be a promising clinical candidate for myocardial injury therapy.